Temporal and spatial characteristics of vegetation coverage and their influencing factors in the Sugan Lake wetland on the northern margin of the Qinghai–Tibet Plateau - Kang, Man-Ping; Zhao, Cheng-Zhang; Li, Xiao-Ya; Ma, Min; Zhao, Xia-Wei (Frontiers in Ecology and Evolution, 2023)
Fractional vegetation cover (FVC) is an important indicator of the development or reversal of salt marsh due to its absence in arid desert areas. Many studies have emphasized the differences in factors that affect fractional vegetation cover (FVC) in different temporal and spatial scales. However, few studies have reported on the temporal and spatial variations in vegetation coverage and their response to climate and also on the hydrological environment in inland salt marsh wetlands. Accordingly, based on a wetland community survey, different types of data, such as meteorological data, hydrological data, and Landsat remote sensing image data, recorded during the period from 1990 to 2020 were collected. The characteristics of the spatial and temporal distribution of vegetation coverage in the Sugan Lake wetland over the past 30 years were analyzed using a binary pixel model. Furthermore, a quantitative analysis on the response of vegetation coverage to hydrological and meteorological factors was undertaken. The results of the present study showed that the dimidiate pixel model had a high simulation accuracy in retrieving the vegetation coverage in inland salt marsh wetlands. The vegetation coverage of the Sugan Lake wetland increased with each year from 1990 to 2020, and its annual average was 19.34%. The spatial distribution of vegetation coverage was patchy and decreased from the center to the edge of the wetland. Within the same period, the vegetation coverage showed an increasing trend in Quan-shui and He-hong areas and a decreasing trend in the Shan-hong area. Vegetation coverage was mainly affected by various factors, such as precipitation, lake area, surface runoff, groundwater depth, and residential density, respectively. It was significantly positively correlated with precipitation (R2 = 0.56, P < 0.01), lake area (R2 = 0.50, P < 0.01), air temperature (R2 = 0.46, P < 0.01), and river system density (R2 = 0.52, P < 0.01) and negatively correlated with groundwater depth (R2 =-0.57, P < 0.01) and residential density (R2 = −0.38, P < 0.05). Implicit in these findings are complex mechanisms of change in vegetation coverage that help prevent the degradation of vegetation in fragile ecosystems.